Higher Education Institutions Grading: Administrative and Support Personnel - Kirillov, Andrey Vladimirovich; Vinichenko, Mikhail Vasilevich; Melnichuk, Alexander Vasilevich; Melnichuk, Yulyia Alexandrovna; Lakina, Yulyia (International Journal of Economics and Financial Issues, 2015)
This article describes main grading principles applied in Russia as well as internationally. The grading system is based on those used by Hay Group and Watson Wyatt. We evaluated existing grading examples for administrative and support personnel, methodology, effectiveness and how it affects performance results in Higher Education Institutions. Based on this, we set goals, principles and established regulatory basis for implementing grading in the University. In addition to this, we studied all possible ways to create effective working group to carry out this task and, its activities and performance in proceeding with administrative and support personnel optimization and organizational reform at large aiming to create a sustainable effective structure in the University. The effectiveness indicators (KPI), their use as well as the positions’ scale, compensation packages and re-designed remuneration system were introduced. Nevertheless, during this process we identified a number of problems that University leadership faced while implementing reform. These problems occurred largely due to personnel non-readiness for cordial changes, lengthy decision making and complex management system (at the level of the Ministry of Higher Education and other related regulatory bodies) that constantly changes during reform system and counter reforms danger. We would like to point out that grading was carried out by University personnel without third party involvement that lead to effective management team formation. Keywords: grading, Hay Group and Watson Wyatt technology, effectiveness indicators, optimization, positions importance, positions assessment, ranking factors, compensation system, remuneration structure, organizational and staff structure. JEL Classifications: I21; I28